LogiQL Syntax - Halpin, Terry (Taylor & Francis Group, 2015)
This appendix provides an overview of LogiQL’s syntax. Its goal is to give a general picture of how LogiQL programs are structured. Hence, some details have been left out and some nuances glossed over. Moreover, you should be aware that even though a program segment is syntactically valid, executing it still may lead to unexpected results or error messages. The notation used in this appendix is a version of EBNF (Extended Backus Naur Form) in which syntax categories are separated from their definitions via ‘::=’ and are terminated with a period (‘.’). Literal text is surrounded by quotation mark symbols (‘"’). Some definitions have alternatives separated by a vertical bar (‘|’), and optional constructs are suffixed with a question mark (‘?’). Appending an asterisk (‘*’) to an item indicates zero or more occurrences of that item, and adding a plus sign (‘+’) indicates one or more occurrences of that item. Finally, parentheses are used to group syntactic elements.